Kinetics of phagocytosis of Staphylococcus aureus by alveolar and peritoneal macrophages. - Pesanti, E L (1979)
The rate of uptake of radiolabeled Staphylococcus aureus by macrophages in vitro was studied by use of Lineweaver-Burk analysis. It was found that competition for ingestion by excess unlabeled particles, either staphylococci or unrelated particles, resulted in diminished uptake of the labeled particles and that opsonization of particles with specific antiserum enhanced that uptake solely by altering the maximum velocity of uptake (Vmax). Uptake of radiolabeled staphylococci opsonized with specific antiserum was not inhibited by excess numbers of unopsonized organisms; the ingestion was inhibited by excess numbers of opsonized unlabeled organisms, and that inhibition was characterized by depression of Vmax. Inhibition of phagocytosis by indoacetate and cytochalasin B resulted from depression in both Vmax and Michaelis constate (Km). In addition, the phagocytic function of macrophages improved during in vitro culture, a phenomenon which was particularly striking for alveolar macrophages. That enhancement of activity resulted from improvements in both Vmax and Km. Addition of opsonizing antibody at any stage of in vitro maturation resulted in further increases in phagocytic uptake, increases which affected only Vmax. The in vitro maturation of phagocytic function by alveolar macrophages could be inhibited by both 2-deoxy-D-glucose and cycloheximide, but not by culture in hypoxia. The data indicate that the terms of Lineweaver-Burk analysis cna be correlated with functional aspects of phagocytosis and that Vmax represents the avidity of the macrophage surface for the particle, whereas Km is an index of the capacity of the cell for ingestion.